2011
DOI: 10.1517/13543776.2011.553800
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin S inhibitors: 2004 – 2010

Abstract: Although > 40 patent applications have appeared between 2004 and 2010, the decrease in applications focusing on cathepsin S over the past 2 - 3 years may reflect a renewed interest in other cathepsins, especially cathepsin K, for which a small molecule inhibitor is currently in Phase III clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 54 publications
0
57
0
Order By: Relevance
“…These compounds have been designed to engage the active site of the target protease and bind to catalytic cysteine residue via the employment of a warhead that is typically electrophilic in nature (Chang et al, 2007). The types of warheads that have been utilised are either irreversible (epoxide, Michael acceptor, α-haloketone) or reversible (cyano, ketoamide) in design (Lee-Dutra et al, 2011).…”
Section: The Therapeutic Utility Of Cathepsin Smentioning
confidence: 99%
“…These compounds have been designed to engage the active site of the target protease and bind to catalytic cysteine residue via the employment of a warhead that is typically electrophilic in nature (Chang et al, 2007). The types of warheads that have been utilised are either irreversible (epoxide, Michael acceptor, α-haloketone) or reversible (cyano, ketoamide) in design (Lee-Dutra et al, 2011).…”
Section: The Therapeutic Utility Of Cathepsin Smentioning
confidence: 99%
“…In-depth analysis of the crystal structure of the CatS highlighted that the S2 and S3 subsites were important to achieve selectivity towards CatS [119,120]. Selective targeting is known to be an issue with many cathepsin inhibitors, and much effort has been dedicated to the development of selectivity whilst maintaining potency [121][122][123]. However, the inherent problems in achieving specific targeting of CatS is not only due to high homology within the active site of several other related family members such as CatL and CatK, but also due to the resultant lysosomotrophism, where accumulation of inhibitors in cathepsin rich organs can result in decreased specificity and increased toxicity issues [124].…”
Section: Cathepsin S Inhibitorsmentioning
confidence: 99%
“…During this process, cysteine cathepsins are believed to be intimately involved in the processing of both the myelin-associated antigens and Ii of MHC-II. Several studies have shown that cathepsin S inhibitors can attenuate EAE and other autoimmune models, suggesting that cathepsin S may be a specific therapeutic target for MS [10, 16, 2527]. In particular, the compound LHVS has been suggested to selectively inhibit cathepsin S and attenuate EAE [12, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Despite years of interest in therapeutically targeting cysteine cathepsins in MS, and sporadic autoimmune clinical trials of lead compounds that inhibit cathepsin S [27], EAE has not been attempted in mice genetically deficient in individual cysteine cathepsins. Hence, the importance of cathepsins B, S, and L as specific therapeutic targets for MS remain unsubstantiated in an animal model.…”
Section: Introductionmentioning
confidence: 99%